KEMAMPUAN PEMBENAH TANAH DALAM MENAHAN LENGAS DAN MENINGKATKAN AKTIVITAS MIKROORGANISME PADA REGOSOL - Jakak Krisdiyanto; Yanisworo W Ratih; R. Agus Widodo; Lelanti Peniwiratri (Jurnal Agrivet, 2026)
Regosol is a soil with a low organic matter content and a predominantly sand fraction, making it permeable to water and not a conducive environment for microbial activity. This study aimed to determine the effect of soil amendments on soil and microbial activity. The study was conducted experimentally using a completely randomized design with two factors. The first factor was the amendment type: manure, charcoal, and a mixture of manure and charcoal in a 1:1 ratio. The second factor was the amendment dosage, which were 2% and 4%. The study was conducted using containers filled with 4 kg of absolutely dry soil. After the amendments were added according to the treatment, the soil was incubated for 60 days at field capacity, followed by another 15 days without water addition, for a total incubation period of 75 days. The data obtained were analyzed using analysis of variance with orthogonal contrasts and the LSD test at the 5% level. The results of the study showed that there was an interaction between the type of amendment and the amendment concentration in increasing the moisture content of field capacity. The highest field capacity value was found in the D2B3 treatment (amendment concentration of 4% d and the amendment type was a mixture of charcoal and manure 1:1, which was 21.01%. The addition of amendment materials to Regosol increased the activity and number of soil microorganisms. The best activity was in the D2 and B3 treatments.